Onomatopoeia in Comic Discourse: A Descriptive Study of Dead Days by Dey - Andi Mulyani; A. Tenrinia Asmanur; Rahmat J (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Abstract This study examines English onomatopoeia in the comic Dead Days by Dey. It aims to identify the types of onomatopoeia and to analyze readers’ ability in understanding their meanings. This research used a descriptive qualitative method. The data were collected from 45 episodes of the comic and a questionnaire given to 30 students of the English and Literature Department at Alauddin State Islamic University of Makassar in the 2017/2018 academic year. The results show that direct onomatopoeia is the most common type, with 20 words identified, followed by 10 associative onomatopoeia words. No exemplary onomatopoeiawas found. The analysis of the questionnaire indicates that the students’ ability to understand the meaning of onomatopoeia is good, with most students scoring between 66 and 75. This study shows that onomatopoeia helps readers understand the comic story and makes the narrative more interesting. It also demonstrates that familiar sounds in comics can support language learning and improve readers’ vocabulary recognition. Furthermore, the findings provide useful information for educators, writers, and linguists about using onomatopoeia in comics and other literary texts. Overall, this research emphasizes the important role of onomatopoeia in comic discourse and its contribution to readers’ understanding and engagement. Keywords: direct onomatopoeia, associative onomatopoeia, readers’ ability, comic discourse